1985
DOI: 10.1161/01.res.56.6.773
|View full text |Cite
|
Sign up to set email alerts
|

The plasma membrane sodium-hydrogen exchanger and its role in physiological and pathophysiological processes.

Abstract: SUMMARY. The plasma membranes of most if not all vertebrate cells contain a transport system that mediates the transmembrane exchange of sodium for hydrogen. The kinetic properties of this transport system include a 1:1 stoichiometry, affinity for lithium and ammonium ion in addition to sodium and hydrogen, the ability to function in multiple 1:1 exchange modes involving these four cations, sensitivity to inhibition by amiloride and its analogues, and allosteric regulation by intracellular protons. The plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
234
3
4

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(249 citation statements)
references
References 145 publications
(141 reference statements)
8
234
3
4
Order By: Relevance
“…Thus, diabetic nephropathy may develop in diabetic patients who are also susceptible to essential hypertension [6,9]. It has been suggested that this exchange may be a mode of operation of the Na+/H + antiport [11]. However, the anucleate erythrocyte does not exhibit Na+/H + exchange at rest [22] and thus is not suitable for measurements of Na § + ant• activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, diabetic nephropathy may develop in diabetic patients who are also susceptible to essential hypertension [6,9]. It has been suggested that this exchange may be a mode of operation of the Na+/H + antiport [11]. However, the anucleate erythrocyte does not exhibit Na+/H + exchange at rest [22] and thus is not suitable for measurements of Na § + ant• activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mahnensmith and Aronson have suggested that this countertransport may be one mode of operation of the ubiquitous Na +/H § antiport [11]. Increased Na +/H + antiport activity was subsequently documented in platelets [12] and leucocytes from hypertensive humans [13,14] and in the spontaneously hypertensive rat [15,16].…”
mentioning
confidence: 99%
“…This ex changer would adjust pHj during alkaline transients or could serve to accumulate Cl-in cells. In most vertebrate cells studied, pHj regulation during acid transients is achieved by an amiloride-sensitive N a + IH + anti porter , often working in conjunction with Na + -dependent or Na + -independent HC03 -1 Cl-exchangers (Mahnensmith and Aronsson, 1985;Boyarsky et aI., 1988b;Frelin et aI., 1988;Grinstein et aI., 1989). Recent studies have identified addi tional mechanisms that influence pHi' e.g., an elec trogenic N a + IHC03 -symporter, which carries HC03 -inward at the expense of the Na + gradient (Boron and Boulpaep, 1983;Deitmer and Schlue, 1987; for reviews see Madshus, 1988;Chesler and Kaila, 1992).…”
mentioning
confidence: 99%
“…SLC activity could be indicative of plasma membrane SHE; the expression of which is repeated in cell types other than erythrocytes. 12 This hypothesis is appealing since it is easy to envisage how a dysfunction of the SHE in vascular smooth muscle (VSM) or kidney cells could contribute to development of hypertension. Increased SHE could result in an increased sodium influx.…”
Section: Discussionmentioning
confidence: 99%